Pengaruh Tenaga Kerja Perempuan Terhadap Pertumbuhan Ekonomi di Nusa Tenggara Barat 2017-2021 - Edi Irawan; Asma Taqiyya (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Every workforce is an important asset in economic growth, but the segregation of sectors in the labor market keeps many women trapped in vulnerable and low-income informal labor. Therefore, this research aims to examine the influence of the female labor force on economic growth in West Nusa Tenggara Province, using quantitative methods and panel data regression analysis. The study involves variables such as Women as Professional Workers, Women's Income Contribution, Average Length of Schooling for Women, and Women's Life Expectancy, with data obtained from the Central Statistics Agency (BPS) of West Nusa Tenggara Province. The results indicate that these four variables do not have a significant impact on economic growth in West Nusa Tenggara Province.